Life satisfaction in specific domains: adaptation of a scale for its evaluation - Schmidt, Vanina (2015)
The aim of this paper is to present the adaptation of the Life Satisfaction Scale in Specific Domains to be used in adults from Buenos Aires. In a first stage, work was done in the linguistic and conceptual equivalence. In the second stage, the local version of the scale was applied to a sample by 187 adults (women = 56.10 %) with an average age of 31.20 (SD = 10.70). We studied the ability of discrimination of items, the reliability, construct validity and content. The results showed that the scale has adequate content validity to be applied in adults of our environment, and presents clear evidence of construct validity and adequate precision for almost all the subscales. The results are discussed in view of the importance of generating new conceptual and instrumental developments relating to the concepts of positive psychology.